Relational Cultural Theory: A Guiding Framework for Study Abroad Experiences - Janee R Avent Harris; Syntia S Dietz; Loni Crumb (Teaching and Supervision in Counseling, 2019)
Faculty led-study abroad programs promote cultural competence and professional and personal development for students. However, students from historically marginalized and underrepresented groups do not participate in these experiences at the same rate as students from majority cultures. Counselor educators must seek ways to recruit diverse populations to promote equity in and access to international education experiences. Relational Cultural Theory (RCT) provides a guiding framework for counselor educators to diversify study abroad programs while also attending to cultural and power dynamics. Implications for counselor educators and recommendations for future research are also included.
Keywords: Relational Cultural Theory; study abroad; counselor education